Human Rights Research and Ethics Review: Protecting Individuals or Protecting the State? - Amon, Joseph J. (Public Library of Science, 2012)
Joseph Amon and colleagues discuss the challenges of conducting human rights research in settings where local research ethics committees may favor the interests of the state over the interests of research participants.